Facile Fabrication of Anisotropic Multicompartmental Microfibers Using Charge Reversal Electrohydrodynamic Co‐Jetting. Issue 1 (10th November 2021) - Lee, Jaeyu; Moon, Seongjun; Han, Yong Bin; Yang, Seung Jae; Lahann, Joerg; Lee, Kyung Jin
Abstract: Anisotropic microstructures are utilized in various fields owing to their unique properties, such as reversible shape transitions or on‐demand and sequential release of drug combinations. In this study, anisotropic multicompartmental microfibers composed of different polymers are prepared via charge reversal electrohydrodynamic (EHD) co‐jetting. The combination of various polymers, such as thermoplastic polyurethane, poly(D, L‐lactide‐co‐glycolide), poly(vinyl cinnamate), and poly(methyl methacrylate), results in microfibers with distinct compositional boundaries. Charge reversal during EHD co‐jetting enables facile fabrication of multicompartmental microfibers with the desired composition and tunable inner architecture, broadening their spectrum of potential applications, such as functional microfibers and cell scaffolds with multiple physical and chemical properties. Abstract : Multicompartmental microfibers composed of diverse polymer combinations are fabricated using charge reversal electrohydrodynamic co‐jetting method. Adjusting parameters such as applied voltage, flow rate, and polymer solution concentration, allows each polymer to stably constitute each compartment of a single microfiber. The anisotropic microfibers can offer distinct chemical and mechanical properties in a single structure.